The roles of a peer-led collaborative learning approach in Ethiopian secondary schools - Feyisa Mulisa; Simeret Kassahun Mekonnen (Bahir Dar Journal of Education)
A collaborative learning with a heightened reputation that enables learners to become competent in the global economy. More than a decade ago, along with this growing concern, peer-led collaborative learning (PLCL) approach has been adopted and stuck into Ethiopian educational systems. By following these actions, there are certain attempts to understand the practices of PLCL in educational settings, however, there are no more studies regarding the role of PLCL for secondary school students. This study is, therefore, intended to examine the hands-on roles of PLCL for secondary school students. The participants in this study were 991 students that were recruited from six public secondary schools via stratified random sampling. Data were collected using questionnaires and focus group discussions whereas analyses were made using descriptive statistical methods and narrative description of data. The findings show that hypothetically the roles of PLCL for secondary school students are considered to be academic, psychosocial and economic. Ironically the approach by far rewards group leaders to do all activities that would be done by each of the group members increases the dependency of middle and low achiever students and becomes a milieu of sexual harassment mainly for female students. Acknowledging more research findings would be warranted, we suggest that the practice of PLCL ought to be arranged towards subject specific task orientation and the quality of mentoring processes should be restructured in the form of more supportive, participative and cooperative ways.